Neurodevelopmental Disorder in a Bulgarian Patient Caused By Novel Mutations in the NARS1 Gene - Atemin S.; Todorov T.; Tourtourikov I.; Mitev V.; Todorova A. (Acta Medica Bulgarica, 2022)
NARS1-related neurodevelopmental disorder is caused by pathogenic variants in the NARS1 gene. The aim of the present study was to determine the genetic reason for the epilepsy and microcephaly, observed in the tested patient. Using whole exome sequencing two novel heterozygous variants c.676G>C, p.Val226Leu and c.986G>A, p.Arg329Gln in the NARS1 gene were detected. The obtained results from the molecular-genetic analysis can enrich the spectrum of epilepsy related variants and can explain the genetic etiology of a severe epileptic disease.